Coexisting Papillary and Clear Renal Cell Carcinoma in the Same Kidney - Murat Ustuner; Busra Yaprak; Kerem Teke; Seyfettin Ciftci; Mucahit Kart; Kursat Yildiz; Melih Culha (Case Reports in Urology)
Renal cell carcinoma (RCC) is the most common solid lesion of the kidney. Bilateral synchronous benign and malignant renal tumors have been defined in some reports. However, unilateral concordance of malignant renal tumors is very rare and there are only a few cases that had synchronous different subtypes of malignant renal tumors arising within the same kidney. Herein, we describe a 67-year-old male patient who had clear cell RCC and papillary RCC in his right kidney that were successfully treated with radical nephrectomy. We also reviewed the pertinent literature.